Mycobacterium bovis in a bull on a university farm: public health implications (2020)
An unsuspected bull in a private herd of forty cattle heads in south-western Nigeria died suddenly following three days´ treatment against tick infestation. Post-mortem findings revealed multifocal widespread nodules in all lobes of the lungs with markedly enlarged lymph nodes. Isolate from cultured sample was subjected to spoligotyping which confirmed the isolate as Mycobacterium bovis (M. bovis) belonging to the SB1027 clade with octal number 676773776277600 (Figure 1). This finding has implications on the health of the cattle handlers considering aerosol inhalation of disseminated bacilli from the lungs of the infected bull through cough sprays. Routine screening of cattle for tuberculosis is therefore emphasized.